2014
DOI: 10.1186/s13047-014-0051-8
|View full text |Cite
|
Sign up to set email alerts
|

Movement of the human foot in 100 pain free individuals aged 18–45: implications for understanding normal foot function

Abstract: BackgroundUnderstanding motion in the normal healthy foot is a prerequisite for understanding the effects of pathology and thereafter setting targets for interventions. Quality foot kinematic data from healthy feet will also assist the development of high quality and research based clinical models of foot biomechanics. To address gaps in the current literature we aimed to describe 3D foot kinematics using a 5 segment foot model in a population of 100 pain free individuals.MethodsKinematics of the leg, calcaneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 37 publications
2
31
1
3
Order By: Relevance
“…Indeed, previous studies were mainly limited to the medial arch, while in reality; all the three arches contribute to support the diverse biomechanical activities of the foot. Moreover, it has been shown that motion of the lateral arch is similar to that of the medial arch [9,14,19,20]; whereas the transverse arch is essential to the stability of both arches [2,22]. Thus, understanding the relationship between the arches of the foot is paramount.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies were mainly limited to the medial arch, while in reality; all the three arches contribute to support the diverse biomechanical activities of the foot. Moreover, it has been shown that motion of the lateral arch is similar to that of the medial arch [9,14,19,20]; whereas the transverse arch is essential to the stability of both arches [2,22]. Thus, understanding the relationship between the arches of the foot is paramount.…”
Section: Introductionmentioning
confidence: 99%
“…Nester et al have pointed great interindividual variation in the movement of foot and ankle joints when normal healthy subjects are subjected to study (Nester 2009;Nester et al 2014). These authors have hypothesized that normal healthy subjects (asymptomatic) can have different and very diverse kinematic patterns that could be considered normal.…”
Section: Discussionmentioning
confidence: 99%
“…En cualquier caso, los errores encontrados son pequeños y dentro del rango esperado (error medio<5 o ). En base a estos resultados, Nester et al (2010) propone un modelo de 4 segmentos del pie (calcáneo, mediopié antepié lateral y antepié medial) , que se ha utilizado para describir la cinemática de 100 sujetos sanos (71 mujeres y 19 hombres) (Nester et al 2014). …”
Section: Modelos Para El Análisis Dinámico De Las Articulaciones Del Pieunclassified
See 2 more Smart Citations